Pembelajaran Berbasis Karakter Nilai - Abduloh Abduloh (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
This paper seeks to describe the concept of implementation and learning outcomes based on character values ​​as an effort to achieve the goals to be achieved by an individual / community group in order to improve lives in the present and the future effective and efficient, so it needs a variety of support resources that must be met so that learning can be implemented optimally. This study uses a concept analysis method of Character-Based Learning Values " concept inquiry through theoretic analysis. The researcher identifies, studies and then studies research data to gain an understanding of the character-based learning values ​​in learning that can be directly observed. Research data were collected through observation and interviews, library research from various theoretical documents. technical analysis of the data used is an interactive model through the stages of data collection, data reductional, data display, and conclusion / verifying. Analytic results of the study 1. Concepts of character-based learning values ​​can be applied and have an impact on the learning process, special in the achievement of predetermined learning goals, in improving skills, knowledge, attitude skills and behavioral skills. 2) The implementation of value-based learning can be carried out with the power of support, teachers, students, parents and the environment, although in its implementation in the educational process can not optimal support the learning process due to limited resources, 3) The results of value-based learning can a conservative role, creative, critical, evaluative, productive and innovative continuous towards improving the benefit of the people.